An evaluation of nanocomposites as pit and fissure sealants in child patients - S Singh; R K Pandey (Wolters Kluwer Medknow Publications, 2011)
Background: Dental caries affects populations of all ages in all the regions of the world, with the child patient being at the highest risk. Fifty percent of the permanent molars are decayed by the age of 12, due to lack of information about protection and occlusal morphology. Pit and fissure sealing undoubtedly plays a fundamental role in preventing occlusal caries. The most common approach to assess the sealing ability of pit and fissure sealants of tooth/restoration is the measurement of dye penetration along the interface. Aims and Objectives: The present study aims to evaluate the microleakage and penetration depth of three different types of dental materials, namely (A) Conventional pit and fissure sealant, (B) Flowable composite, (C) Flowable nanocomposite. Study Design: This in-vitro comparative study comprised of extracted human posterior teeth mounted as blocks. Materials and Methods: In the present study, microleakage and penetration depths of conventional sealants/flowable composite and nanocomposite were measured with the help of a dye under stereomicroscope. Statistical Analysis: A student't' test and Analysis of variance (ANOVA) tests were performed to compare the mean microleakage and penetration depth. Results: Microleakage was found to be highest for the flowable composites, and least for the conventional sealant. The nanocomposite values were intermediate. Penetration depth was highest for nanocomposite and least for flowable composite. Conclusions: According to the results, the nanocomposite was found to be an excellent dental material for penetration in deep pits and fissures, though it exhibits mild microleakage. Hence, it can be recommended for use in pediatric dental patients, as a pit and fissure sealing agent.